The Design Of Perimeter Intrusion Detection System (PIDS) Surveillance Alarm Using USB Webcam And Artificial Intelligence Based On Web And Telegram Bot At Medan Aviation Polytechnic - Zhafirah Rizki Fadilah Lbs; Tiara Sylvia; Darmeli Nasution (Jurnal Scientia, 2024)
Medan Aviation Polytechnic is a civil service college under the auspices of the Ministry of Transportation, especially in the air dimension. Medan Aviation Polytechnic is equipped with various complete educational facilities. However, security issues arise when cadets try to exploit vulnerabilities in the area to escape the campus. The purpose of PIDS is to detect and provide early warning of infiltration attempts in the campus area. This system is designed to integrate with various technology components such as the web and telegram bots as direct notifications and warnings to security officers, thereby increasing the security of Medan Aviation Polytechnic cadets. The method used in this research is by conducting research design, tool design, providing tool components and conducting system testing when the tool as a whole has been completed. The results of this study indicate that the system runs according to the desired design, where notifications are made with documentation in the form of camera portrait images and live streaming with a USB Webcam integrated with Artificial Intelligence (AI). If there is movement detected, it will send the portrait results to Telegram and issue an alarm on the buzzer and live streaming can be accessed on the available website.